Pengaruh Kualitas Layanan dan Harga Terhadap Kepuasan Konsumen pada Hotel Nugraha Unaaha Kabupaten Konawe - Melati Melati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to determine and explain the effect of service quality and price on customer satisfaction at Hotel Nugraha Unaaha, Konawe Regency. The population in this study were consumers in Hotel Nugraha Unaaha, Konawe Regency, which numbered 50 people. This study uses multiple linear regression analysis. Simultaneously there is a significant influence variable service quality and price on customer satisfaction. This fact shows that the better the quality of service provided and the more appropriate the price given, the higher the customer satisfaction at Hotel Nugraha Unaaha, Konawe Regency. Service quality variables have a significant effect on customer satisfaction. The better the quality of service provided, the higher the customer satisfaction at Hotel Nugraha Unaaha, Konawe Regency. This fact shows that the better quality of service contributes to increasing customer satisfaction. Price variables have a significant effect on customer satisfaction. The more suitable the price set by the company, the higher the customer satisfaction at Hotel Nugraha Unaaha, Konawe Regency. This fact shows that the more appropriate the price set by the company has a contribution in increasing customer satisfaction.